Emtricitabine-induced pure red cell aplasia - Nithendra Manickchund; Camille du Plessis; Melanie-Anne A. John; Thandekile C. Manzini; Bernadett I. Gosnell; Richard J. Lessells; Yunus S. Moosa (AOSIS, 2019)
Introduction: Anemia is common in HIV. Parvo B19 infection is a well-recognised cause of red cell aplasia. Other causes of persistent pure red cell aplasia (PRCA) include anti-retroviral drugs such as zidovudine and lamivudine. We describe a case of PRCA that strongly implicates emtricitabine as the probable cause. Patient presentation: Patient was HIV positive and on treatment with a fixed drug combination consisting of tenofovir, emtricitabine and efavirenz for 3 months when she developed severe transfusion dependent anemia. The anemia, attributed to PRCA, was persistent and transfusion dependent for about one year. Management and outcome: Replacement of emtricitabine with abacavir resulted in a prompt, complete and lasting resolution of the anaemia, suggesting an etiologic role of emtricitabine in the PRCA. Conclusion: Emtricitibine is a rare cause of pure red cell aplasia.